Llama-3.1-70B Accuracy Degradation Under Acoustic Perturbations in MMSU Emotional Intent Classification - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 2 peer-reviewed papers addressing the following research question: What is the accuracy degradation of Llama-3.1-70B on MMSU emotional intent classification when acoustic features are perturbed. 10 claims were extracted from source literature; 10 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 8.7/10. This report is a machine-generated literature synthesis and does not constitute ori
Machine-generated literature synthesis.